The Prognostic Value of Hyponatremia and Hypokalemia in Acute Myocardial Infarction Patients - شيخ ابراهيم, عبد الله; الأبرص, أحمد (Latakia University Journal -Medical Sciences Series, 2020)
Syria is one of the countries with a high risk of ischemic heart disease. It is one of the most causes of morbidity and mortality worldwide. Myocardial infarction does not mean simply occlusion of an epicardial artery. Rather, it is a systemic, metabolic and neurohormonal process that affects and is affected by other systems, including blood ions. In this research, we will study the changes of sodium and potassium in patients with myocardial infarction and their impact in prognosis. This study included 100 patients. Patients were divided into two groups, a high-risk group and a low-risk group based on the GRACE score, and successive laboratory tests were made for both sodium and potassium from admission to discharge. We found the incidence of the hyponatremia was 54% and hypokalemia was 64%. We found that early hyponatremia was associated with short-term prognosis (p-value = 0.001), and hyponatremia at discharge was associated with long-term prognosis (p-value = 0.003). We found that early hypokalemia was associated with short-term prognosis (p-value = 0.001). We found a significant association between the development of cardiac shock and hyponatremia (p-value = 0.001, OR = 40.1), and significant association between the development of arrhythmias and hypokalemia (p-value = 0.002, OR = 41.9). We also found that the return of values ​​to normal ranges at discharge indicates improvement and response to treatment.